Hepatic Sarcoidosis Presenting as Cholestatic Liver Injury Exacerbated by Nitrofurantoin Use - Halloran, Sean J (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.